The phenomenon of culture and its role in the formation of personality information culture - N.V. Volkova (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the questions of the role of information culture during forming af total general culture of man of modem society. It contains a characteristic oflevebof information competence.